(3JMaI GdWdGH aj TQM fRgI GdMSGHs - (3GdOeTbj GdTGaYj, GdUaOj, CHh GdaVd, NWjH GdYGOdjI, eMeO Hf CMeO Hf eMeO Hf CjhH, (B905 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3abO cfJ aj MGd GdWahdI hGdTHGH GTJZdJ HYdej GdaQGFV hGdMSGH hbQCJ ajgeG cJHG TgjQI hMQQJ ajgeG bhGYO cKjQI hCJbfJ efgeG eSGFd ZRjQI hfaGFS NWjQI hQGLYJ ajgeG eDdaGJ LeI (B...s
(3BNQgG (B:s
... (3hJcSjQ GdbWYI hgh eVQhH WhdgG aj YQVgG CQHYI CPQY MGUdI ef VQH SJI aj KdGKjf hgh GdeKef hGdNeSI hGdYTQhf gj GdSYQ ceG JbOe aGdKef GdeLghd GdeSDhd Yfg CQHYI hCQHYI GJSGY (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\98s
(3Pjd cTa GdXfhf dBb HQRc WgQGfj (B\ (3U (B28s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs